Description of larvae of the Feather Blenny, Hypsoblennius hentz (Pisces: Blenniidae), from New York Waters - Schmidt, Robert E.; Moccio, Paul A. (Zootaxa, 2013)
Hypsoblennius hentz (Lesueur) larvae are described from specimens recently collected in the vicinity of New York Harbor and Raritan Bay. Previous descriptions (Hildebrand and Cable 1938) were erroneous and additionally we provide the first yolk-sac larval descriptions for Western Atlantic Hypsoblennius. H. hentz larvae are distinguished from the other Atlantic species by the size and distribution of preopercular spines.